Nitrogen Fertilizer and Growth Regulator Impacts on Tuber Deformity, Rot, and Yield for Russet Potatoes. (1st July 2012) - Reiter, Mark S.; Rideout, Steven L.; Freeman, Joshua H.
Abstract : Potatoes ( Solanum tuberosum ) are an important high-value commodity for producers in the Mid-Atlantic Region. Current production recommendations were based on white potatoes, and practices for Russet potatoes have not been researched in this region. The objective of this study was to test impacts of N rate (0, 67, 134, 201, and 268 kg N ha −1 ), N application timing (100% applied with planter, 2-way split (30% with planter and 70% band applied approximately 30 days after planting at dragoff), and three-way split (30% with planter, 50% band applied prior to drag-off, and 20% band applied at first sight of bloom)), and additions of the growth regulator maleic hydrazide (MH-30). We tested "Goldrush" and "Norkotah" Russet potato varieties on marketability, total yield, tuber deformity, and tuber soft rot incidence for sandy loam soils in the Mid-Atlantic. Overall, year variations were significant with substantial rots (up to 86.5%) occurring in year 3. Maleic hydrazide and N application timing had little consistent effect on any tested parameter. Nitrogen rate and variety factors had the greatest impacts on deformity, tuber rots, and yields for Russet potatoes in the Mid-Atlantic Region with 134 kg N ha −1 producing the highest total yields in 2009 and 2010. If tuber rots can be controlled, both "Goldrush" and "Norkotah" are acceptable varieties under the Mid-Atlantic production practices.